Diagnosing nephrogenic systemic fibrosis in the post‐FDA restriction era. Issue 5 (5th June 2014) - Thomson, Laura K.; Thomson, Peter C.; Kingsmore, David B.; Blessing, Karen; Daly, Conal D.; Cowper, Shawn E.; Roditi, Giles H.
<x xml:space="preserve">Abstract</x> The emergence of an association between gadolinium‐based contrast agents (GBCA) and the rare condition nephrogenic systemic fibrosis (NSF) led to a warning in 2006 from the Food and Drug Administration (FDA) restricting the use of the GBCAs to patients with an estimated glomerular filtration rate of >30 mL/min/1.73m2. We discuss our experience with a post‐FDA restriction presentation of NSF and subsequent patient death in which the prolonged lead‐time of ∼5.5 years led to challenges in ensuring a secure diagnosis of NSF and establishing risk exposures. Accurate contemporary records of contrast administration and clinical factors alongside clinical and pathological expertise ensured that we were able to confidently diagnose NSF, despite the length of lead time and confounding factors. J. Magn. Reson. Imaging 2015;41:1268–1271. © 2014 Wiley Periodicals, Inc.